Soft Skills: Rankings in the Assessment of Entrepreneurs and the Participation of HEIs in Their Formation - M. A. Lukashenko; E. V. Alekseeva (Высшее образование в России)
The problem of forming and developing soft skills has not lost its relevance for many years. It is believed that possession of these skills ensures the subject’s competitiveness in the labor market. A special role is played by the formation of flexible skills in entrepreneurs, who allow them to be more adaptive to changes, interact effectively with the internal and external environment, find non-standard solutions in difficult situations, thereby increasing the efficiency and competitiveness of their own business.The purpose of our research is to compile a rating of soft skills in the assessment of existing entrepreneurs and to identify the degree of participation of higher education institutions in their formation. The data are obtained empirically from a study of 360 entrepreneurs. They show the undeniable importance for entrepreneurs of developing soft skills and, in most cases, their underdevelopment at the proper level. The paper presents the results of a survey demonstrating the proportion of entrepreneurs who have developed a particular skill in the process of self-education (19-38%), as well as the proportion of entrepreneurs who received an education at a university (0-22%) or in additional education programs in other organizations ( 1-13%). The study found that between 33 and 73% of entrepreneurs surveyed had not received soft skills training. Entrepreneurs ranked communication management (opinion of 76% of respondents) and decision making (73%) as the most important skills for their activities; the most developed were decision making (30%) and customer focus (28%). The work provides recommendations to universities in terms of increasing their presence in the market of additional education in order to develop soft skills among entrepreneurs as a factor in increasing their competitiveness.